Monitoring Climate Change Impacts: Metrics at the Intersection of the Human and Earth Systems - National Research Council (The National Academies Press, 2010)
The stresses associated with climate change are expected to be felt keenly as human population grows to a projected 9 billion by the middle of this century, increasing the demand for resources and supporting infrastructure. Therefore, information to assess vulnerabilities to climate change is needed to support policies and investments designed to increase resilience in human and Earth systems. There are currently many observing systems that capture elements of how climate is changing, for example, direct measurements of atmospheric and ocean temperature. Although those measurements are essential for understanding the scale and nature of climate change, they do not necessarily provide information about the impacts of climate change on humans that are especially relevant for political and economic planning and decision making. Monitoring Climate Change Impacts tackles the challenge of developing an illustrative suite of indicators, measurements (and the locations around the globe where the measurements can be applied), and metrics that are important for understanding global climate change and providing insight into environmental sustainability. Eight panels provided input on: cryosphere, land-surface and terrestrial ecosystems, hydrology and water resources, atmosphere, human health and other dimensions, oceans (both physical and biological\/chemical), and natural disasters. The book also provides an illustrative set of metrics that are likely to be affected by climate change over the next 20-25 years and, when taken together, can potentially give advance warning of climate-related changes to the human and environment systems.

America's Climate Choices - National Research Council
Climate change is occurring. It is very likely caused by the emission of greenhouse gases from human activities, and poses significant risks for a range of human and natural systems. And these emissions continue to increase, which will result in further change and greater risks. America's Climate Choices makes the case that the environmental, economic, and humanitarian risks posed by climate change indicate a pressing need for substantial action now to limit the magnitude of climate change and to prepare for adapting to its impacts. Although there is some uncertainty about future risk, acting now will reduce the risks posed by climate change and the pressure to make larger, more rapid, and potentially more expensive reductions later. Most actions taken to reduce vulnerability to climate change impacts are common sense investments that will offer protection against natural climate variations and extreme events. In addition, crucial investment decisions made now about equipment and infrastructure can \

Advancing the Science of Climate Change - National Research Council (The National Academies Press, 2010)
Climate change is occurring, is caused largely by human activities, and poses significant risks for2014and in many cases is already affecting2014a broad range of human and natural systems. The compelling case for these conclusions is provided in Advancing the Science of Climate Change, part of a congressionally requested suite of studies known as America's Climate Choices. While noting that there is always more to learn and that the scientific process is never closed, the book shows that hypotheses about climate change are supported by multiple lines of evidence and have stood firm in the face of serious debate and careful evaluation of alternative explanations. As decision makers respond to these risks, the nation's scientific enterprise can contribute through research that improves understanding of the causes and consequences of climate change and also is useful to decision makers at the local, regional, national, and international levels. The book identifies decisions being made in 12 sectors, ranging from agriculture to transportation, to identify decisions being made in response to climate change. Advancing the Science of Climate Change calls for a single federal entity or program to coordinate a national, multidisciplinary research effort aimed at improving both understanding and responses to climate change. Seven cross-cutting research themes are identified to support this scientific enterprise. In addition, leaders of federal climate research should redouble efforts to deploy a comprehensive climate observing system, improve climate models and other analytical tools, invest in human capital, and improve linkages between research and decisions by forming partnerships with action-oriented programs.

Adapting to the Impacts of Climate Change - National Research Council (The National Academies Press, 2010)
Across the United States, impacts of climate change are already evident. Heat waves have become more frequent and intense, cold extremes have become less frequent, and patterns of rainfall are likely changing. The proportion of precipitation that falls as rain rather than snow has increased across the western United States and Arctic sea ice has been reduced significantly. Sea level has been rising faster than at any time in recent history, threatening the natural and built environments on the coasts. Even if emissions of greenhouse gases were substantially reduced now, climate change and its resulting impacts would continue for some time to come. To date, decisions related to the management and protection of the nation's people, resources, and infrastructure have been based on records in the recent past, when climate was relatively stable. Adapting to the Impacts of Climate Change, part of the congressionally requested America's Climate Choices suite of studies, calls for a new paradigm-one that considers a range of possible future climate conditions and impacts that may be well outside the realm of past experience. Adaptation requires actions from many decision makers in federal, state, tribal, and local governments; the private sector; non-governmental organizations; and community groups. However, current efforts are hampered by a lack of solid information about the benefits, costs, and effectiveness of various adaptation options; climate information on regional and local scales; and a lack of coordination. Adapting to the Impacts of Climate Change calls for a national adaptation strategy that provides needed technical and scientific resources, incentives to begin adaptation planning, guidance across jurisdictions, shared lessons learned, and support of scientific research to expand knowledge of impacts and adaptation.

Informing an Effective Response to Climate Change - National Research Council (The National Academies Press, 2010)
Global climate change is one of America's most significant long-term policy challenges. Human activity2014especially the use of fossil fuels, industrial processes, livestock production, waste disposal, and land use change2014is affecting global average temperatures, snow and ice cover, sea-level, ocean acidity, growing seasons and precipitation patterns, ecosystems, and human health. Climate-related decisions are being carried out by almost every agency of the federal government, as well as many state and local government leaders and agencies, businesses and individual citizens. Decision makers must contend with the availability and quality of information, the efficacy of proposed solutions, the unanticipated consequences resulting from decisions, the challenge of implementing chosen actions, and must consider how to sustain the action over time and respond to new information. Informing an Effective Response to Climate Change, a volume in the America's Climate Choices series, describes and assesses different activities, products, strategies, and tools for informing decision makers about climate change and helping them plan and execute effective, integrated responses. It discusses who is making decisions (on the local, state, and national levels), who should be providing information to make decisions, and how that information should be provided. It covers all levels of decision making, including international, state, and individual decision making. While most existing research has focused on the physical aspect of climate change, Informing an Effective Response to Climate Change employs theory and case study to describe the efforts undertaken so far, and to guide the development of future decision-making resources. Informing an Effective Response to Climate Change offers much-needed guidance to those creating public policy and assists in implementing that policy. The information presented in this book will be invaluable to the research community, especially social scientists studying climate change; practitioners of decision-making assistance, including advocacy organizations, non-profits, and government agencies; and college-level teachers and students.

Limiting the Magnitude of Future Climate Change - National Research Council
Climate change, driven by the increasing concentration of greenhouse gases in the atmosphere, poses serious, wide-ranging threats to human societies and natural ecosystems around the world. The largest overall source of greenhouse gas emissions is the burning of fossil fuels. The global atmospheric concentration of carbon dioxide, the dominant greenhouse gas of concern, is increasing by roughly two parts per million per year, and the United States is currently the second-largest contributor to global emissions behind China. Limiting the Magnitude of Future Climate Change, part of the congressionally requested America's Climate Choices suite of studies, focuses on the role of the United States in the global effort to reduce greenhouse gas emissions. The book concludes that in order to ensure that all levels of government, the private sector, and millions of households and individuals are contributing to shared national goals, the United States should establish a \

A Transportation Research Program for Mitigating and Adapting to Climate Change and Conserving Energy: Special Report 299 - Transportation Research Board (The National Academies Press, 2009)
In reviewing proposals for transportation research programs as part of reauthorizing the federal surface transportation program, the Transportation Research Board recognized a gap: no proposals explicitly addressed research to mitigate GHG emissions and energy consumption attributable to passenger and freight travel or to adapt to climate change. A Transportation Research Program for Mitigating and Adapting to Climate Change and Conserving Energy is the product of a study to suggest research programs to fill this and other perceived gaps. Specifically, this book identifies research needs with regard to policies and strategies relating to the use of the transportation system and to assist infrastructure owners in adapting to climate change; focuses on research programs that could provide guidance to officials at all levels responsible for policies that affect the use of surface transportation infrastructure and its operation, maintenance, and construction; and aims to help officials begin to adapt the infrastructure to climate changes that are already occurring or that are expected to occur in the next several decades.

Global Climate Change and Extreme Weather Events: Understanding the Contributions to Infectious Disease Emergence: Workshop Summary - Institute of Medicine
Long before the \

Sea-Level Rise for the Coasts of California, Oregon, and Washington: Past, Present, and Future - National Research Council (The National Academies Press, 2012)
Tide gauges show that global sea level has risen about 7 inches during the 20th century, and recent satellite data show that the rate of sea-level rise is accelerating. As Earth warms, sea levels are rising mainly because ocean water expands as it warms; and water from melting glaciers and ice sheets is flowing into the ocean. Sea-level rise poses enormous risks to the valuable infrastructure, development, and wetlands that line much of the 1,600 mile shoreline of California, Oregon, and Washington. As those states seek to incorporate projections of sea-level rise into coastal planning, they asked the National Research Council to make independent projections of sea-level rise along their coasts for the years 2030, 2050, and 2100, taking into account regional factors that affect sea level. Sea-Level Rise for the Coasts of California, Oregon, and Washington: Past, Present, and Future explains that sea level along the U.S. west coast is affected by a number of factors. These include: climate patterns such as the El Nino, effects from the melting of modern and ancient ice sheets, and geologic processes, such as plate tectonics. Regional projections for California, Oregon, and Washington show a sharp distinction at Cape Mendocino in northern California. South of that point, sea-level rise is expected to be very close to global projections. However, projections are lower north of Cape Mendocino because the land is being pushed upward as the ocean plate moves under the continental plate along the Cascadia Subduction Zone. However, an earthquake magnitude 8 or larger, which occurs in the region every few hundred to 1,000 years, would cause the land to drop and sea level to suddenly rise.

Seasonal to Decadal Predictions of Arctic Sea Ice: Challenges and Strategies - National Research Council (The National Academies Press, 2012)
Recent well documented reductions in the thickness and extent of Arctic sea ice cover, which can be linked to the warming climate, are affecting the global climate system and are also affecting the global economic system as marine access to the Arctic region and natural resource development increase. Satellite data show that during each of the past six summers, sea ice cover has shrunk to its smallest in three decades. The composition of the ice is also changing, now containing a higher fraction of thin first-year ice instead of thicker multi-year ice. Understanding and projecting future sea ice conditions is important to a growing number of stakeholders, including local populations, natural resource industries, fishing communities, commercial shippers, marine tourism operators, national security organizations, regulatory agencies, and the scientific research community. However, gaps in understanding the interactions between Arctic sea ice, oceans, and the atmosphere, along with an increasing rate of change in the nature and quantity of sea ice, is hampering accurate predictions. Although modeling has steadily improved, projections by every major modeling group failed to predict the record breaking drop in summer sea ice extent in September 2012. Establishing sustained communication between the user, modeling, and observation communities could help reveal gaps in understanding, help balance the needs and expectations of different stakeholders, and ensure that resources are allocated to address the most pressing sea ice data needs. Seasonal-to-Decadal Predictions of Arctic Sea Ice: Challenges and Strategies explores these topics.

A National Strategy for Advancing Climate Modeling (The National Academies Press, 2012)
As climate change has pushed climate patterns outside of historic norms, the need for detailed projections is growing across all sectors, including agriculture, insurance, and emergency preparedness planning. A National Strategy for Advancing Climate Modeling emphasizes the needs for climate models to evolve substantially in order to deliver climate projections at the scale and level of detail desired by decision makers, this report finds. Despite much recent progress in developing reliable climate models, there are still efficiencies to be gained across the large and diverse U.S. climate modeling community. Evolving to a more unified climate modeling enterprise-in particular by developing a common software infrastructure shared by all climate researchers and holding an annual climate modeling forum-could help speed progress. Throughout this report, several recommendations and guidelines are outlined to accelerate progress in climate modeling. The U.S. supports several climate models, each conceptually similar but with components assembled with slightly different software and data output standards. If all U.S. climate models employed a single software system, it could simplify testing and migration to new computing hardware, and allow scientists to compare and interchange climate model components, such as land surface or ocean models. A National Strategy for Advancing Climate Modeling recommends an annual U.S. climate modeling forum be held to help bring the nation's diverse modeling communities together with the users of climate data. This would provide climate model data users with an opportunity to learn more about the strengths and limitations of models and provide input to modelers on their needs and provide a venue for discussions of priorities for the national modeling enterprise, and bring disparate climate science communities together to design common modeling experiments. In addition, A National Strategy for Advancing Climate Modeling explains that U.S. climate modelers will need to address an expanding breadth of scientific problems while striving to make predictions and projections more accurate. Progress toward this goal can be made through a combination of increasing model resolution, advances in observations, improved model physics, and more complete representations of the Earth system. To address the computing needs of the climate modeling community, the report suggests a two-pronged approach that involves the continued use and upgrading of existing climate-dedicated computing resources at modeling centers, together with research on how to effectively exploit the more complex computer hardware systems expected over the next 10 to 20 years.

A Review of the U.S. Global Change Research Program's Draft Strategic Plan - National Research Council
The U.S. government supports a large, diverse suite of activities that can be broadly characterized as \

Ocean Acidification: Starting with the Science - National Research Council (The National Academies Press, 2011)
Over recent years, human activities such as the burning of fossil fuels have increased the amount of carbon dioxide gas emitted to the atmosphere2014and the amount that dissolves into the ocean. Now, so much carbon dioxide has been absorbed by the ocean that the chemistry of seawater is changing, causing the ocean to become more acidic. Based on a National Research Council report, this booklet describes the well-understood chemistry of ocean acidification and explores the many questions that remain: How will ocean acidification impact marine life such as fish, corals, and shellfish? How will the effects on individual species scale up to whole ecosystems? What will ocean acidification mean for aquaculture, the fishing industry, and coastal tourism?

Next Generation Earth System Prediction: Strategies for Subseasonal to Seasonal Forecasts - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
As the nation's economic activities, security concerns, and stewardship of natural resources become increasingly complex and globally interrelated, they become ever more sensitive to adverse impacts from weather, climate, and other natural phenomena. For several decades, forecasts with lead times of a few days for weather and other environmental phenomena have yielded valuable information to improve decision-making across all sectors of society. Developing the capability to forecast environmental conditions and disruptive events several weeks and months in advance could dramatically increase the value and benefit of environmental predictions, saving lives, protecting property, increasing economic vitality, protecting the environment, and informing policy choices. Over the past decade, the ability to forecast weather and climate conditions on subseasonal to seasonal (S2S) timescales, i.e., two to fifty-two weeks in advance, has improved substantially. Although significant progress has been made, much work remains to make S2S predictions skillful enough, as well as optimally tailored and communicated, to enable widespread use. Next Generation Earth System Predictions presents a ten-year U.S. research agenda that increases the nation's S2S research and modeling capability, advances S2S forecasting, and aids in decision making at medium and extended lead times.

Assessment of Approaches to Updating the Social Cost of Carbon: Phase 1 Report on a Near-Term Update - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The social cost of carbon (SCC) for a given year is an estimate, in dollars, of the present discounted value of the damage caused by a 1-metric ton increase in CO2 emissions into the atmosphere in that year; or equivalently, the benefits of reducing CO2 emissions by the same amount in that given year. The SCC is intended to provide a comprehensive measure of the monetized value of the net damages from global climate change from an additional unit of CO2, including, but not limited to, changes in net agricultural productivity, energy use, human health effects, and property damages from increased flood risk. Federal agencies use the SCC to value the CO2 emissions impacts of various policies including emission and fuel economy standards for vehicles, regulations of industrial air pollutants from industrial manufacturing, emission standards for power plants and solid waste incineration, and appliance energy efficiency standards. There are significant challenges to estimating a dollar value that reflects all the physical, human, ecological, and economic impacts of climate change. Recognizing that the models and scientific data underlying the SCC estimates evolve and improve over time, the federal government made a commitment to provide regular updates to the estimates. To assist with future revisions of the SCC, the Interagency Working Group on the Social Cost of Carbon (IWG) requested the National Academies of Sciences, Engineering, and Medicine complete a study that assessed the merits and challenges of a limited near-term update to the SCC and of a comprehensive update of the SCC to ensure that the estimates reflect the best available science. This interim report focuses on near-term updates to the SCC estimates.

Strategic Issues Facing Transportation, Volume 2: Climate Change, Extreme Weather Events, and the Highway System: Practitioner’s Guide and Research Report - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 750: Strategic Issues Facing Transportation, Volume 2: Climate Change, Extreme Weather Events, and the Highway System: Practitioner2019s Guide and Research Report provides guidance on adaptation strategies to the likely impacts of climate change through 2050 in the planning, design, construction, operation, and maintenance of infrastructure assets in the United States (and through 2100 for sea-level rise).In addition to the practitioner2019s guide and research report, this project also developed the following items:2022 A software tool that runs in common web browsers and provides specific, region-based information on incorporating climate change adaptation into the planning and design of bridges, culverts, stormwater infrastructure, slopes, walls, and pavements.2022 Tables that provide the same information as the previously mentioned software tool, but in a spreadsheet format that can be printed.2022 Two spreadsheets that illustrate examples of the benefit-cost analysis of adaptation strategies discussed in Appendix B of Part I of NCHRP Report 750, Volume 2.These three items are available on a CD-ROM that is included with a print version of the report. The CD-ROM is also available for download from TRB2019s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.2022 Help on Burning an .ISO CD-ROM Image.2022 Download the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)NCHRP Report 750, Volume 2 is the second in a series of reports being produced by NCHRP Project 20-83: Long-Range Strategic Issues Facing the Transportation Industry. Major trends affecting the future of the United States and the world will dramatically reshape transportation priorities and needs. The American Association of State Highway and Transportation Officials (AASHTO) established the NCHRP Project 20-83 research series to examine global and domestic long-range strategic issues and their implications for state departments of transportation (DOTs); AASHTO's aim for the research series is to help prepare the DOTs for the challenges and benefits created by these trends.Other volumes in this series currently available include:2022 NCHRP Report 750: Strategic Issues Facing Transportation, Volume 1: Scenario Planning for Freight Transportation Infrastructure Investment2022 NCHRP Report 750: Strategic Issues Facing Transportation, Volume 3: Expediting Future Technologies for Enhancing Transportation System Performance2022 NCHRP Report 750: Strategic Issues Facing Transportation, Volume 4: Sustainability as an Organizing Principle for Transportation Agencies2022 NCHRP Report 750: Strategic Issues Facing Transportation, Volume 5: Preparing State Transportation Agencies for an Uncertain Energy Future2022 NCHRP Report 750: Strategic Issues Facing Transportation, Volume 6: The Effects of Socio-Demographics on Future Travel DemandCD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively \

Ocean Acidification: A National Strategy to Meet the Challenges of a Changing Ocean - National Research Council (The National Academies Press, 2010)
The ocean has absorbed a significant portion of all human-made carbon dioxide emissions. This benefits human society by moderating the rate of climate change, but also causes unprecedented changes to ocean chemistry. Carbon dioxide taken up by the ocean decreases the pH of the water and leads to a suite of chemical changes collectively known as ocean acidification. The long term consequences of ocean acidification are not known, but are expected to result in changes to many ecosystems and the services they provide to society. Ocean Acidification: A National Strategy to Meet the Challenges of a Changing Ocean reviews the current state of knowledge, explores gaps in understanding, and identifies several key findings. Like climate change, ocean acidification is a growing global problem that will intensify with continued CO2 emissions and has the potential to change marine ecosystems and affect benefits to society. The federal government has taken positive initial steps by developing a national ocean acidification program, but more information is needed to fully understand and address the threat that ocean acidification may pose to marine ecosystems and the services they provide. In addition, a global observation network of chemical and biological sensors is needed to monitor changes in ocean conditions attributable to acidification.

National Security Implications of Climate Change for U.S. Naval Forces - National Research Council (The National Academies Press, 2011)
In response to the Chief of Naval Operations (CNO), the National Research Council appointed a committee operating under the auspices of the Naval Studies Board to study the national security implications of climate change for U.S. naval forces. In conducting this study, the committee found that even the most moderate current trends in climate, if continued, will present new national security challenges for the U.S. Navy, Marine Corps, and Coast Guard. While the timing, degree, and consequences of future climate change impacts remain uncertain, many changes are already underway in regions around the world, such as in the Arctic, and call for action by U.S. naval leadership in response. The terms of reference (TOR) directed that the study be based on Intergovernmental Panel on Climate Change (IPCC) scenarios and other peer-reviewed assessment. Therefore, the committee did not address the science of climate change or challenge the scenarios on which the committee's findings and recommendations are based. National Security Implications of Climate Change for U.S. Naval Forces addresses both the near- and long-term implications for U.S. naval forces in each of the four areas of the TOR, and provides corresponding findings and recommendations. This report and its conclusions are organized around six discussion areas2014all presented within the context of a changing climate.

Attribution of Extreme Weather Events in the Context of Climate Change - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
As climate has warmed over recent years, a new pattern of more frequent and more intense weather events has unfolded across the globe. Climate models simulate such changes in extreme events, and some of the reasons for the changes are well understood. Warming increases the likelihood of extremely hot days and nights, favors increased atmospheric moisture that may result in more frequent heavy rainfall and snowfall, and leads to evaporation that can exacerbate droughts. Even with evidence of these broad trends, scientists cautioned in the past that individual weather events couldn't be attributed to climate change. Now, with advances in understanding the climate science behind extreme events and the science of extreme event attribution, such blanket statements may not be accurate. The relatively young science of extreme event attribution seeks to tease out the influence of human-cause climate change from other factors, such as natural sources of variability like El Niño, as contributors to individual extreme events. Event attribution can answer questions about how much climate change influenced the probability or intensity of a specific type of weather event. As event attribution capabilities improve, they could help inform choices about assessing and managing risk, and in guiding climate adaptation strategies. This report examines the current state of science of extreme weather attribution, and identifies ways to move the science forward to improve attribution capabilities.

Enhancing Participation in the U.S. Global Change Research Program - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. As the understanding of global change has evolved over the past decades and as demand for scientific information on global change has increased, the USGCRP has increasingly focused on research that can inform decisions to cope with current climate variability and change, to reduce the magnitude of future changes, and to prepare for changes projected over coming decades. Overall, the current breadth and depth of research in these agencies is insufficient to meet the country's needs, particularly to support decision makers. This report provides a rationale for evaluating current program membership and capabilities and identifying potential new agencies and departments in the hopes that these changes will enable the program to more effectively inform the public and prepare for the future. It also offers actionable recommendations for adjustments to the methods and procedures that will allow the program to better meet its stated goals.